Nurturing Software. - Shah, Rajiv C.; Kesan, Jay P. (Communications of the ACM, 2005)
The article discusses the development of computer software. Software is nurtured and cultivated in several different environments from universities to firms. In each environment software is nurtured differently, which in turn influence the final features of software. This simple observation has important implications not only for software development, but also for society. Scholars studying software have emphasized that software designs contain biases that favor certain actors or social values. The article argues that an important source of values in software is the institution in which it is developed. An institution is composed of a group of actors who are subject to a system of rules that structures their activities. These rules concern goals, rights, procedures, social norms, and formal legal rules that attenuate individual preferences. The purpose of this institution is to expand the frontiers of knowledge. Many significant computing technologies have emerged from universities including the Internet, artificial intelligence, and computer graphics.